(untitled) (BIRDEM Medical Journal, 2016)
Peripartum cardiomyopathy is a rare affliction of healthy, young, females characterized by congestive heart failure, intracardiac thrombus, and frequently death. PPCM is associated with a hypercoagulative state, which can cause thromboembolic complications, may be, the initial demonstration off peripartum cardiomyopathy, which is usually an intracardiac thrombosis. Lower extremity embolism is uncommon. We present a case of 22 yr old female a known case of preeclamtic toxaemia associated with bronchial asthma underwent caesarian section at 36 wks of pregnancy & developed severe respiratory distress and needed mechanical ventilation. Two weeks after delivery she developed low back pain with parasthesia of both lower limbs associated with shortness of breath & diagnosed as a case of infra-renal aortic thrombus extending down to common illiac arteries associated with postpartum dilated cardiomyopathy and admitted at our hospital for embolectomy. Infiltration anaesthesia and conscious sedation with invasive monitoring was planned. Surgery and anaesthesia proceeded uneventfully. Birdem Med J 2015; 5(1): 50-53